Monogalactosyldiacylglycerol synthesis in the outer envelope membrane of chloroplasts is required for enhanced growth under sucrose supplementation - Murakawa, Masato; Shimojima, Mie; Shimomura, Yuichi; Kobayashi, Koichi; Awai, Koichiro; Ohta, Hiroyuki (Frontiers in Plant Science, 2014)
Plant galactolipid synthesis on the outer envelope membranes of chloroplasts is an important biosynthetic pathway for sustained growth under conditions of phosphate (Pi) depletion. During Pi starvation, the amount of digalactosyldiacylglycerol (DGDG) is increased to substitute for the phospholipids that are degraded for supplying Pi. An increase in DGDG concentration depends on an adequate supply of monogalactosyldiacylglycerol (MGDG), which is a substrate for DGDG synthesis and is synthesized by a type-B MGDG synthase, MGD3. Recently, sucrose was suggested to be a global regulator of plant responses to Pi starvation. Thus, we analyzed expression levels of several genes involved in lipid remodeling during Pi starvation in Arabidopsis thaliana and found that the abundance of MGD3 mRNA increased when sucrose was exogenously supplied to the growth medium. Sucrose supplementation retarded the growth of the Arabidopsis MGD3 knockout mutant mgd3 but enhanced the growth of transgenic Arabidopsis plants overexpressing MGD3 compared with wild type, indicating the involvement of MGD3 in plant growth under sucrose-replete conditions. Although most features such as chlorophyll content, photosynthetic activity, and Pi content were comparable between wild-type and the transgenic plants overexpressing MGD3, sucrose content in shoot tissues decreased and incorporation of exogenously supplied carbon to DGDG was enhanced in the MGD3-overexpressing plants compared with wild type. Our results suggest that MGD3 plays an important role in supplying DGDG as a component of extraplastidial membranes to support enhanced plant growth under conditions of carbon excess.